IDENTIFIKASI METABOLIT SEKUNDER DAN POTENSI ANTIDIARE EKSTRAK DAUN CINCAU (Stephania capitata (Blume) Spreng) - Ika Ayu Mentari; Indah Hairunisa; Arsyik Ibrahim; Aditya Fridayanti (Jurnal Ilmiah Manuntung, 2019)
Indonesia biodiversity has the second highest number of indigenous medical plants after the amazon rain forest, meanwhile Indonesian people usually used plants as a medicine source and some medicine plants have been developed as modern drugs. One of medicine plant in Indonesia that usually used as a refreshment was grass jelly (Stephania capitata (Blume) Spreng). This plant frequently found in Sumatra, Borneo and Java island and the leaf of grass jelly has been reported as a medicine against stomach complaint (diarrhea) and fevers. This research was designed to investigate the secondary metabolites and the efficacy of leaf extract of grass jelly as anti diarrhea. The leaves extraction was done by using maceration with ethanol solvent at room temperature. Meyer reagent, dagendroff reagent, methanol, magnesium band, hydrochloric acid, iron (III) chloride, anhydrous acetic acid, sulfuric acid, chloroform were used for identification of secondary metabolites from grass jelly leaves. For potency anti diarrhea, animals were divided into six group: diarrhea group, treatment group with loperamid HCl and treatment group of leaf extract of grass jelly. The results showed that the leaf extract of grass jelly contain saponin, phenol, sterol and triterpen and the treatment with leaf extract of grass jelly significantly decreasing time duration of diarrhea.